TRAINING OF MAKING THEMATIC LEARNING MEDIA FOR TEACHERS OF ELEMENTARY SCHOOL HADI SAKTI MATARAM - Muhardini, Sintayana; Mariyati, Yuni; Winata, Aliahardi; Sehabuddin, Ahmad (Indonesian Journal of Devotion and Empowerment, 2019)
It is hoped that the thematic learning media-based bulletin board display training can overcome the problems that exist in schools related to the lack of attractive and effective thematic learning media in the classroom. Bulletin board is one of the types of display media in the form of display media or bulletin boards that can be placed anywhere in the classroom that is open so that it can be read and seen at any time by students even though the material in certain learning has been completed i explained Development of thematic learning media based on bulletins display boards are expected to shape the literacy abilities of children . The long-term goal of developing this learning media is that all elementary schools can carry out learning activities supported by thematic media that are interesting and effective. The development model used in this study is a procedural model that is a descriptive model proposed by Borg & Gall (1983). This training is a follow up to the media development that has been carried out. The training at SD Hadi Sakti went smoothly, the benefits of this training were felt in the process of implementing learning in the classroom. Pelatihan media pembelajaran tematik berbasis bulletin board display diharapkan dapat mengatasi masalah yang ada di sekolah yang berkaitan dengan minimnya media pembelajaran tematik yang menarik dan efektif di kelas. Bulletin board merupakan salah satu jenis media display yang berupa media pajangan atau papan buletin yang bisa ditempatkan dimana saja didalam kelas yang sifatnya terbuka sehingga bisa dibaca dan dilihat kapan saja oleh siswa meskipun materi dalam pembelajaran tertentu telah selesai dijelaskan Pengembangan media pembelajaran tematik berbasis bulletin board display diharapkan dapat membentuk kemampuan literasi anak. Tujuan jangka panjang dari pengembangan media pembelajaran ini adalah agar seluruh Sekolah Dasar dapat melaksanakan kegiatan pembelajaran dengan di dukung media pembelajaran tematik yang menarik dan efektif. Model pengembangan yang digunakan dalam penelitian ini adalah model prosedural yaitu model yang bersifat deskriptif yang dikemukakan oleh Borg & Gall (1983). Pelatihan ini adalah tindak lanjut dari pengembangan media yang sudah dilakukan. Pelatihan di SD Hadi Sakti berjalan lancar, manfaat dari pelatihan ini sangat terasa dalam proses pelaksanaan pembelajaran di kelas.